PENINGKATAN KETERAMPILAN MENULIS DESKRIPSI SISWA KELAS X-3 SMA NEGERI 1 JANTHO MAKMUR DENGAN TEKNIK KONFERENSI - Rudiati Rudiati (Jurnal Dedikasi Pendidikan, 2017)
The purpose of this research is to describe writing description learning using conference technique. The assumption of this research are (1) student class X-3 at SMA Negeri 1 Jantho ability in writing description using conference technique to write description is still low, (2) conference technique is able to uplifting liveliness of student in writing description learning because the learning is conducted individually and team, (3) conference technique is able to uplifting student motivation in description writing learning because process in writing description can make student happy, (4) conference technique is able to uplifting student achievement in writing description, (5) each of student of class X-3 SMA Negeri 1 Jantho Makmur have different character because student ability is heterogeneous. This research use qualitative approach. Kind of research is classroom action research. Action research is conducted in two cycles. Each action is consisting of four actions that are (1) planning, (2) realization, (3) observation, and (4) reflection. Data collecting in this research was done by using observation, interview, field note, documentation, student composition. Research processes cover four phases. First, prewriting cover chosening writing topic based on theme, developing writing topic, deciding title, developing writing topic as a sentence suitable with topic, composing writing framework suitable with topic. Draft phase cover compiling composition draft by showing main idea and detail based on composition framework, and compiling details using conjunction correctly. Editing phase cover editing composition draft by sharing with friend, editing composition, and rewrite composition draft based on suggestion from his friend. Publication phase cover reading composition n front of the class with correct intonation, giving respons to composition which has been read clearly, and rewrite composition well based on suggestion from friend. Result of this research show that skill of students of class X-3 at SMA Negeri 1 Jantho in writing description using conference technique will be described as follows. At cycle I, student average value is 63,7. At cycle I student average value is 74,28. Thereby, it is mean that applying of conference technique is uplifting student ability in writing description